2015
DOI: 10.11159/jbb.2015.002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cellulolytic Organisms from the Gut Contents of Termites Native to Nepal and Their Utility in Saccharification and Fermentation of Lignocellulosic Biomass

Abstract: Lignocellulose is one of the most abundant renewable materials that could serve as a source for fermentable sugars. However, its commercial deployment is limited by the fact that lignocellulose is recalcitrant and requires heroic efforts to release sugars. Although very few, there are cellulose degrading organisms in nature that can efficiently degrade the cellulosic biomass and one among them is termite. Termites are responsible for mass turnover of the cellulosic biomass and they accomplish this task by harb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The pure colonies from each isolates were grown in 50 mL medium containing (g/L) 0.2 K 2 HPO 4 , 0.01 MgSO 4 , 1 NaCl, 0.5 NaNO 3 , 0.05% yeast extract and 10 g CMC according to Sharma et al (2015). Cultures were incubated at 37 °C for 72 h. At the end of incubation 1 mL of each culture suspension was centrifuged at 5000 rpm for 10 min and the pellets were re-suspended in fresh medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pure colonies from each isolates were grown in 50 mL medium containing (g/L) 0.2 K 2 HPO 4 , 0.01 MgSO 4 , 1 NaCl, 0.5 NaNO 3 , 0.05% yeast extract and 10 g CMC according to Sharma et al (2015). Cultures were incubated at 37 °C for 72 h. At the end of incubation 1 mL of each culture suspension was centrifuged at 5000 rpm for 10 min and the pellets were re-suspended in fresh medium.…”
Section: Methodsmentioning
confidence: 99%
“…The Congo red screening assay for cellulase production showed the widest zone of hydrolysis (38 mm) for Aspergillus sp. (Sharma et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to Sharma, Bacillus. sp S3B8 isolated from termites gut was also produced maximum CMCase at pH 7 [10].…”
Section: Effect Of Ph On the Cmcase Activitymentioning
confidence: 95%
“…It is believed that the temperature influences the secretion of extracellular enzyme by possibly changing/or altering the physical properties of the cell membrane. Bacillus grew best at 37 °C in numerous reports [5,6,10].…”
Section: Effect Of Temperature On Cmcase Activitymentioning
confidence: 99%
“…The results obtained are similar with the previous studies. Sharma et al, 2015 found optimum pH at 7 for endoglucanase activity by Bacillus sp. isolated from termite.…”
Section: Effect Of Temperature Ph and Incubation Period On Cmcase Acmentioning
confidence: 99%